Time-Space Dynamics of Return and Circular Migration: Theories and Evidence - Amelie F. Constant (Global Labor Organization (GLO), 2020)
This chapter undertook the monumental task of providing a complete outlook about return, repeat, circular and onward migration by bringing together the perspectives of the host and the home country. In this endeavor, it reviewed and evaluated all theories about why people move, when they circulate, where they go, who are the people who migrate, who are the people who return, and how they change the economic and social structures in the home country. In the process, it revealed the new norm of joint decision-making by the family as a unit and underlined the importance of non-economic reasons for return. The chapter further provided a state-of-the-art literature review about empirical evidence regarding the disparate phenomena of return, circular and onward migration. It emphasized commonalities and compared differences in findings, while connecting them to the theories, policies and institutions. Return, repeat, and circular migrants are self-selected and extremely heterogeneous people and cannot conform under one theory or empirical study. Their de facto migration comportment can be understood by several different theories and, in the absence of good data, it can be explained by a variety of studies. The chapter ends with a critical conclusion and hope to inspire new avenues of research on the topic.
Keywords: F22; J15; J18; J20; J61; 330; Return; circular; onward; international labor migration; public policy